TEACHING VOCABULARIES IN PRIMARY EDUCATION - Abduvoxidova Feruza Yo‘lchi qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article analyzes effective methods for developing vocabulary in teaching English in primary education. Vocabulary is a key element of language learning, which plays an important role in the development of all types of speech activity of students. The  main  goal  of  the  study  is  to  identify  modern,  interactive  and  learner-centered methods for teaching new words to young students. The research used a qualitative analysis method, and scientific sources and practical experiences were studied. The results showed that games, visual aids, songs and context-based teaching methods help students  learn  words  quickly  and  effectively.  Also,  the  processes  of  repetition  and reinforcement  play  an  important  role.  In  conclusion,  the  use  of  innovative  and interactive  approaches  to  teaching  vocabulary  in  primary  education  significantly increases the effectiveness of education.